The Investigation on the Beam Spatial Intensity Distributions in the Injection-Seeded Terahertz Parametric Generator - Jie Zang; Dong Wu; Xingyu Zhang; Zhenhua Cong; Zengguang Qin; Xiaohan Chen; Zhaojun Liu; Ping Li; Feilong Gao; Chenyang Jia; Yue Jiao; Weitao Wang; et al. (IEEE Photonics Journal)
In terahertz (THz) wave parametric sources, the large angle between the pump and terahertz waves (about 65° in LiNbO3 crystal) will affect the spatial intensity distributions. To investigate how the noncollinear phase-matching affects the spatial intensity properties of the pump, Stokes, and THz waves, we take the injection-seeded THz-wave parametric generator (is-TPG) as an example to study the beam spatial intensity properties via the numerical solutions of the coupled-wave equations. The simulated results demonstrate that the pump and Stokes intensities have significant changes along the THz-wave propagation direction. It is the first time that the spatial intensity distributions of the three waves in the THz-wave parametric sources have been studied in theory. In addition, the output intensity distributions of the pump, Stokes, and THz waves are measured in the designed is-TPG. The measured spatial intensity distributions are in coincidence with the simulated results. Investigations on the beam spatial intensity properties provide a potential approach to improve the THz-wave outputs and the pump conversion efficiency for the is-TPG and other THz-wave parametric sources.